Indocyanine green fluorescence videoangiography for reliable variations of supraclavicular artery flaps - Yushi Suzuki; Yusuke Shimizu; Shogo Kasai; Shun Yamazaki; Masashi Takemaru; Takuya Kitamura; Saori Kawakami; Takeshi Tamura (Archives of Plastic Surgery, 2019)
Background Pedicled flaps are useful for reconstructive surgery. Previously, we often used vascularized supraclavicular flaps, especially for head and neck reconstruction, but then shifted to using thoracic branch of the supraclavicular artery (TBSA) flaps. However, limited research exists on the anatomy of TBSA flaps and on the use of indocyanine green (ICG) fluorescence videoangiography for supraclavicular artery flaps. We utilized ICG fluorescence videoangiography to harvest reliable flaps in reconstructive operations, and describe the results herein. Methods Data were retrospectively reviewed from six patients (five men and one woman: average age, 54 years; range, 48–60 years) for whom ICG videoangiography was performed to observe the skin perfusion of a supraclavicular flap after it was raised. Areas where the flap showed good enhancement were considered to be favorable for flap survival. The observation of ICG dye indicated good skin perfusion, which is predictive of flap survival; therefore, we trimmed any areas without dye filling and used the remaining viable part of the flap. Results The flaps ranged in size from 13×5.5 cm to 17×6.5 cm. One patient received a conventional supraclavicular flap, four patients received a TBSA flap, and one patient received a flap that was considered to be intermediate between a supraclavicular flap and a TBSA flap. The flaps completely survived in all cases, and no flap necrosis was observed. Conclusions The TBSA flap is very useful in reconstructive surgery, and reliable flaps could be obtained by using ICG fluorescence videoangiography intraoperatively.